2011
DOI: 10.1037/a0022729
|View full text |Cite
|
Sign up to set email alerts
|

Use of self-help materials for anxiety and depression in mental health services: A national survey of psychologists in Norway.

Abstract: How do psychologists in clinical practice perceive and use self-help materials for clients with anxiety and depression? The use of self-help materials with guidance from a therapist has been suggested as a way of meeting the increasing need for mental health services. The present study investigated factors relevant to the use of self-help materials for the treatment of anxiety and depression among psychologists employed in mental health services. Among 1863 eligible clinical psychologists in Norway, 815 (43.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…Internet-delivered CBT is a new and untraditional treatment format in public health care in Norway. One cannot exclude the possibility that attitudes and expectations among the assessors regarding this treatment format can have biased their ratings of treatment outcome (Nordgreen & Havik, 2011). In addition, we only found moderator effects of diagnosis on outcome on CSR and not on self-reporting.…”
Section: Discussioncontrasting
confidence: 57%
“…Internet-delivered CBT is a new and untraditional treatment format in public health care in Norway. One cannot exclude the possibility that attitudes and expectations among the assessors regarding this treatment format can have biased their ratings of treatment outcome (Nordgreen & Havik, 2011). In addition, we only found moderator effects of diagnosis on outcome on CSR and not on self-reporting.…”
Section: Discussioncontrasting
confidence: 57%
“…This is however somewhat higher than what has been found for individual CBT in a meta-analysis by Cooper and Conklin (2015) . Nordgreen and Havik (2011) identified this concern in a survey among Norwegian psychologists, in which a majority of the sample reported that they believed that client compliance would be higher in individual therapy compared to guided self-help treatment. However, the findings in the present study and a recent meta-analysis (e.g., van Ballegooijen et al, 2014 ) indicate that treatment adherence in guided iCBT is at a comparable level as of individual face-to-face CBT.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of a recent study suggest that it is important to train therapists specifically in conducting guided self-help treatment (Paxling et al, 2013). Self-help treatment in this format is a new and unfamiliar treatment form in Norway and is associated with skepticism among many clinicians (Nordgreen & Havik, 2011). Moreover, in contrast to most other studies on this issue, the self-help treatment was offered as a "low-intensity" treatment in a stepped care model.…”
Section: Self-help Compared With Face-to-face Treatmentmentioning
confidence: 99%